2008
DOI: 10.1007/s00701-008-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Chordoid glioma of the third ventricle

Abstract: Mortality in the immediate postoperative period is 32% and is higher after gross total resection as compared to subtotal resection. Non-fatal postoperative complications are hypothalamic disorders and mental alterations. Gross total resection is the treatment of choice since no recurrence has been reported after macroscopically complete resection, but this is often difficult because of the location and adherence to the hypothalamus. The role of postoperative radiotherapy is uncertain. There is some indication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Poor prognosis might be due to the tumor location in the deep structure of the brain, making it difficult to approach surgically. The possible cause of death and unfortunate poor prognosis of our case is consistent with previously reported cases 9,11,17,25,28) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Poor prognosis might be due to the tumor location in the deep structure of the brain, making it difficult to approach surgically. The possible cause of death and unfortunate poor prognosis of our case is consistent with previously reported cases 9,11,17,25,28) .…”
Section: Discussionsupporting
confidence: 92%
“…Radiological findings from neuroimaging studies of this tumor were also consistent and typical, in that they characteristically exhibit a well-circumscribed border, uniform contrast enhancement, and a fusiform gross morphology 2,19,27,28) . On the histological side, it was cautiously suggested that the tumor showed features of ependymal differentiation 6,19,23,25) .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…10,18,21) Among 54 of 55 patients treated by surgery, 27 had gross total removal (GTR), 22 had partial removal (PR), and 5 cases were biopsied. No recurrence was reported for a long duration after GTR, 5,8,12,28,39) but five patients (22.7%) had recurrence after PR. GTR carries significant risk because of the close relationship between the tumor and the critical organs nearby.…”
Section: Discussionmentioning
confidence: 99%